Air Passenger Transport in Europe Before and During The COVID-19 Pandemic Versus Economic Security - Maciej STAJNIAK; Bartosz KOZICKI (Communications of International Proceedings, 2021)
The study compares the number of people transported by air transport in 26 European countries in 2019-2020 in homonymous periods (January-June). Multidimensional comparative analyzes were used for the research. Raw data was grouped and untangled. Categorized line and bar charts were used for the analyzes, ranking the raw data under consideration and comparing their measures in the form of arithmetic averages and medians. The analyzes used indexes of dynamics with a constant basis. For illustrative purposes, some of the charts have been divided to highlight the observed significant changes in the number of passengers transported by air in 26 European countries in dynamic terms. The study ends with a summary and conclusions.
Keywords: Passenger Air Transport; Multivariate Analyzes; Economic Security